2018
DOI: 10.1371/journal.pntd.0006587
|View full text |Cite
|
Sign up to set email alerts
|

Mapping dengue risk in Singapore using Random Forest

Abstract: BackgroundSingapore experiences endemic dengue, with 2013 being the largest outbreak year known to date, culminating in 22,170 cases. Given the limited resources available, and that vector control is the key approach for prevention in Singapore, it is important that public health professionals know where resources should be invested in. This study aims to stratify the spatial risk of dengue transmission in Singapore for effective deployment of resources.Methodology/principal findingsRandom Forest was used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 28 publications
(24 reference statements)
2
73
0
1
Order By: Relevance
“…Despite the strengths of our study, our RF approach is likely to generate time lags in forecasting rapid changes in dengue, which is also a common occurrence with other forecasting approaches. Including a predictor of mosquito abundance from an entomological surveillance program may reduce such time lag errors [71]. However, this type of data was not available at the national level given insufficient temporal and spatial granularity.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Despite the strengths of our study, our RF approach is likely to generate time lags in forecasting rapid changes in dengue, which is also a common occurrence with other forecasting approaches. Including a predictor of mosquito abundance from an entomological surveillance program may reduce such time lag errors [71]. However, this type of data was not available at the national level given insufficient temporal and spatial granularity.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Para além das limitações, o presente estudo mostrou que a espacialização de doenças de alta magnitude para a realidade brasileira evidencia os contrastes territoriais de condições de saúde associados a fatores determinantes de adoecimentos. A técnica utilizada para identificação de áreas críticas também se mostrou adequada no sentido de orientar as ações de vigilância no âmbito nacional no que tange a necessidade de maior articulação com as vigilâncias locais e demais setores, para implementação de ações conjuntas que possam dirimir os problemas de saúde causados por doenças infecciosas e parasitárias e outros fatores a elas relacionadas (30).…”
Section: Discussionunclassified
“…A study by [10] used a Random Forest approach that predicts the risk rank of dengue transmission in Singapore with dengue; population, entomological and environmental data. The predicted risk ranks are then categorized and mapped to color-coded risk groups which were evaluated with dengue cases and cluster data.…”
Section: Related Studiesmentioning
confidence: 99%
“…Results of the study revealed a 26.9% of the variation of DHF patients using a number of water storage containers, Aedes Aegypti in drainage of refrigerators, pH and temperature of water in container. In the study by Ong et al [7] predicting the Dengue incidence with the use of Random Forest approach, predicted the risk rank of dengue transmission in Singapore with dengue cases, population, entomological and environmental data. The evaluation using the latest dengue case data in the study showed a strong predictive ability for the model, compared to the study results of Tilwani, Dave, & Nadurbarkar [8], that adopted a regression approach with Poisson Regression and Negative Binomial to investigate the correlation between dengue incidence and climatic fluctuations including relative humidity, temperature, and pressure.…”
Section: Introductionmentioning
confidence: 99%